Symptomatic cholelithiasis patients have an increased risk of pancreatic cancer: A population‐based study. Issue 5 (22nd September 2020) - Wang, Chi‐Chih; Tseng, Ming‐Hseng; Wu, Sheng‐Wen; Yang, Tzu‐Wei; Chen, Hsuan‐Yi; Sung, Wen‐Wei; Su, Chang‐Cheng; Wang, Yao‐Tung; Chen, Wei‐Liang; Lai, Hsueh‐Chou; Lin, Chun‐Che; Tsai, Ming‐Chang
Abstract: Background and Aim: Pancreatic cancer is a fatal disease; currently, the risk factor survey is not suitable for sporadic pancreatic cancer, which has neither family history nor the genetic analysis data. The aim of the present study was to evaluate the roles of cholelithiasis and cholelithiasis treatments on pancreatic cancer risk. Methods: Symptomatic adult patients with an index admission of cholelithiasis were selected from one million random samples obtained between January 2005 and December 2009. The control group was matched with a 1:1 ratio for sex, age, chronic pancreatitis, and pancreatic cystic disease. Subsequent pancreatic cancer, which we defined as pancreatic cancer that occurred ≥ 6 months later, and total pancreatic cancer events were calculated in the cholelithiasis and control groups. The cholelithiasis group was further divided into endoscopic sphincterotomy/endoscopic papillary balloon dilatation, cholecystectomy, endoscopic sphincterotomy/endoscopic papillary balloon dilatation and cholecystectomy, and no‐intervention groups for evaluation. Results: The cholelithiasis group and the matched control group included 8265 adults. The cholelithiasis group contained 86 cases of diagnosed pancreatic cancer, and the control group contained 8 cases ( P < 0.001). The incidence rate ratio (IRR) of subsequent pancreatic cancer was significantly higher in the cholelithiasis group than in the control group (IRR: 5.28, P < 0.001). The IRR of subsequent pancreatic cancer was higher in the no‐intervention group comparing with cholecystectomy group (IRR = 3.21, P = 0.039) but was similar in other management subgroups. Conclusion: Symptomatic cholelithiasis is a risk factor for pancreatic cancer; the risk is similar regardless of the intervention chosen for cholelithiasis.